Analisis Kompetensi dan Disiplin Terhadap Kinerja Pegawai Melalui Motivasi Sebagai Variabel Mediasi - Palahudin Palahudin; Hastanti Ismah Rahayu; Ismartaya Ismartaya (IPM2KPE, 2023)
This study aims to find the direct effect and the total effect of competence and work discipline on employee performance as well as the indirect effect of competence and discipline through motivation as a mediating variable. This research method is descriptive analysis, verification, and Path Analysis and Sobel Test testing. The results showed that the variables of competence and work discipline had a positive direct effect on work motivation. Competency, discipline and work motivation variables have a significant direct effect on employee performance. Motivation mediates the indirect effect between competence and employee performance but does not mediate the indirect effect between discipline and employee performance. In conclusion, that competence and discipline are very important in an employee's performance through motivation. Keywords: Discipline, Competence, Employee Performance, Work Motivation